Discussion of Inconsiderate Cruelty Towards Animals: Further Arguments for Animal Rights - Maduka, Enyimba; Awugosi, Chukwuemeka I.; Ohere, Pius A.; Okpe , Timothy Adie; Essien, Joseph Paul (Studia Ecologiae et Bioethicae, 2024)
This work focuses primarily on animal rights in the United States within the context of the specific legal system existing in that country. It argues that animal rights as recognized by state law are limited, in the sense that enforcement can occur only through public prosecution. If horses and cows are beaten and mistreated at a local farm, or if greyhounds are forced to live in small cages, protection will come only if the prosecutor decides to provide it. However, as prosecutors have limited budgets, and animal protection is rarely a priority the result is that violations of state law occur every day. We contend that there is no good reason to accept the level of suffering that is now being experienced by millions of living creatures. Doubts have been raised about the radical idea that animals deserve to have “autonomy”, understood as a right to be free from human control and use. In our view, the primary focus should instead be on animal welfare and suffering. While animals should not be treated merely as tools for human purposes, it is possible for humans to control them in ways that still allow animals to have decent lives. However, emphasis on minimizing suffering and ensuring decent lives for animals has significant implications. It is appropriate to consider human interests in this equation, because most times human interests take precedence over those of animals. Adopting the conversational method of inquiry, we claim that often the interests of animals are entirely disregarded, and if they were considered, many of our current practices would be indefensible.